Digital mono-pulse method in cylindrical antenna - Leśniak, W.; Marszal, J.; Salamon, R.; Rudnicki, M.; Schmidt, A. (Archives of Acoustics, 2006)
The article presents a method designed to improve the accuracy of cylindrical antenna multi-beam sonar performance. The method is based on the mono-pulse method used in radars and sonars. It provides good bearing accuracy in a single sounding action. The only change required is the generation of two deflected beams and some simple computations. The new approach to mono-pulse technique, with application of digital signal processing is presented in the paper. The computer simulations proved, that good bearing accuracy can be obtained even for a relatively low signal to noise ratio.